Remodeling of the intercalated disc related to aging in the mouse heart. Issue 3 (September 2016) - Bonda, Tomasz A.; Szynaka, Beata; Sokołowska, Magdalena; Dziemidowicz, Magdalena; Winnicka, Maria M.; Chyczewski, Lech; Kamiński, Karol A.
Abstract: Background: Aging is related to declined cardiac hemodynamic function. As pumping performance may be significantly related to slowed ventricular depolarization and non-synchronous contraction, we hypothesized that aging may cause dysfunction of intercalated disc (ID), which is the structure responsible for intercellular electrical communication between cardiomyocytes. Methods: Male C57BL/6J mice were used for the study at two ages: 4 and 24 months. Electrocardiographic recording was made to analyze the time of ventricular depolarization. Then mice were killed, and the hearts were harvested for examination in transmission electron microscopy (TEM) and immunofluorescence imaging. The expression of connexin 43 (Cx43), N-cadherin, and β-catenin in the myocardium of the left ventricle was evaluated using Western blotting. Results: In senescent mice, analysis of averaged QRS complex showed its significant prolongation. At the ultrastructural level, we found frequent disruptions of the ID (affecting 29 ± 5% of them), mainly at the site of adherens junction, with relatively preserved desmosomal intercellular connections and diminished number of gap junctions. Western blotting revealed significantly decreased abundance of Cx43 protein in aged animals, which may cause slowed impulse propagation through the gap junctions and contribute to the observed electrocardiographic alterations. The level of RNA for Cx43 is similar between young and old animals, which suggests a post-transcriptional mechanism of Cx43 protein downregulation. Conclusions: Our study shows age-related disorganization of ID, which may be responsible for slowed conduction of the depolarization wave within the heart, and supports the hypothesis of cardiac dysfunction in senescence.